PATTERNS OF THE EVOLUTION OF APTYCHI OF MIDDLE JURASSIC TO EARLY CRETACEOUS BOREAL AMMONITES - Rogov, M.A.; Mironenko, A.A. (My University, 2016)
Here we are providing a review of aptychi records in ammonites of Boreal origin or that inhabited Boreal/Subboreal basins during the Bathonian–Albian with special focus on new records and the relationship between the evolution of ammonite conch and aptychi. For the first time we figure aptychi that belong to Aulacostephanidae, Virgatitidae, Deshayesitidae, Craspeditinae and Laugeitinae. A strong difference between aptychi of micro- and macroconchs of co-occurring Aspidoceratidae is shown, which, along with their shell morphologies suggests niche divergence of these dimorphs. Aptychi of Aptian Sinzovia (Aconeceratidae) should be tentatively ascribed to Diday-ilamellaptychus, while their previous assignment to rhynchaptychi was caused by misidentification. Aptychi of Middle Jurassic–Early Cretaceous Boreal and Subboreal ammonites are characterized by a very thin calcareous non-porous outer layer lacking distinct ribs and tubercles (only radial striae sometimes occur), and mainly should be assigned to Praestriaptychus. Some ammonoid groups (i.e. Ancylocerina and Desmoceratoidea) are characterized by the presence of different aptychi types irrespective of their shell shape. This fact could indicate that bivalved praestriaptychi could have easily transformed into single-valved ‘‘anaptychi’’ and vice versa. Size and form of aptychi in relation to those of the aperture of ammonite conchs vary within different lineages and at least some Stephanoceratoidea and Perisphinctoidea have aptychi significantly smaller than the aperture diameter.
Keywords: Aptychi; Jurassic; Cretaceous; Ammonites; Evolution; Mesozoic::Cretaceous; Mesozoic::Jurassic; Мезозой::Юрская; Мезозой::Меловая